The Allocation of Resources by Voting - Barzel, Yoram; Sass, Tim R. (Quarterly Journal of Economics, 1990)
A general theory of voting, which explains under what conditions voting will be chosen as a means for allocating resources and how the constitution that governs the voting will be structured is presented. It is hypothesized that developers of voting organizations will structure their organizations in order to maximize the value of shares sold by minimizing the expected costs of wealth transfer and decision making in the voting organization. Implications regarding the allocation of votes and assessments within the organization, the domain of voting decisions, and the optimal voting rule are tested with data on the constitutional structure of condominium homeowner associations.